Organization of Administrative Judiciary - Radošević, Ratko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Judicial review of administration is the result of the rule of law and of the principle of legality of administration. Special administrative judiciary, however, exists only in civil law countries and it is associated with a special administrative law. In this paper, the author explains the organization of administrative judiciary in France, Germany and Austria, because of their great influence on other countries. Then, the author pays a special attention to the organization of administrative judiciary in Serbia. After a brief historical rewiew of the development of administrative judiciary, all the factors that affect the organization of the administrative judiciary are analyzed in detail. The author concludes that present organization is not appropriate, and that the reform is necessary. More administrative courts should be established, but introducing a two-instance administrative judiciary should be carefully considered.